Pendampingan Penguatan Kompetensi Guru Daerah Perbatasan Berbasis Pembelajaran Berbasis Deep Learning untuk Menjawab Tantangan Keterampilan Abad ke-21 - Jewarut, Siprianus; Usman, Usman; Sumarni, Margaretha Lidya; Alnija, Marianus Dinata (Jurnal Pengabdian UNDIKMA, 2025)
This community service program aims to enhance the competencies of teachers in the Indonesia–Malaysia border area through the application of a Deep Learning-based instructional approach to address the challenges of 21st-century skills. The implementation employed the Co-M-F-oR-T method (coaching, mentoring, facilitation, and training), involving 23 teachers in Bengkayang Regency as participants. The evaluation instruments consisted of questionnaires analyzed descriptively. The results of the program indicate an improvement in participants’ understanding by 75% and an 80% effectiveness rate in mentoring activities. These findings demonstrate that the mentoring process was effective and contributed to improving teachers’ knowledge and competencies in developing teaching modules based on the Deep Learning approach.